Brentuximab vedotin compared with other therapies in relapsed/refractory Hodgkin lymphoma post autologous stem cell transplant: median overall survival meta-analysis. (July 2015) - Bonthapally, Vijayveer; Yang, Hongbo; Ayyagari, Rajeev; Tan, Ruo-Ding; Cai, Sean; Wu, Eric; Gautam, Ashish; Chi, Andy; Huebner, Dirk
Abstract Objective: This meta-analysis compared the median overall survival (mOS) of brentuximab vedotin reported in the pivotal phase 2 study with published results of other therapies for the treatment of relapsed/refractory (R/R) Hodgkin lymphoma (HL) post autologous stem cell transplant (ASCT). Research design and methods: A systematic literature review identified studies that reported survival outcomes following conventional/experimental therapies in R/R HL patients, with ≥50% having failed ≥1 ASCT. Kaplan–Meier curves were used to reconstruct individual patient level survival data. Patients were grouped by treatment type and reconstructed data were used to estimate the mOS. Censored median regression modeling was used to compare mOS in each group with the mOS in the pivotal brentuximab vedotin trial. All patients in the pivotal trial had undergone ASCT, therefore a sensitivity analysis was conducted among studies with a 100% post-ASCT patient population. Results: The mOS reported for brentuximab vedotin was 40.5 (95% CI 30.8–NA) compared with 26.4 months (95% CI 23.5–28.5) across all 40 studies identified (n = 2518 excluding the brentuximab vedotin trial) (p < 0.0001). The difference in mOS between brentuximab vedotin and chemotherapy, allogeneic stem cell transplant (allo-SCT), and other therapies, was 17.7 (95% CI 10.6–24.7; p < 0.0001), 12.5 (95% CI 8.2–16.9; p < 0.0001), and 15.2 months (95% CI 4.9–25.5; p = 0.0037), respectively. For the 11 studies reporting a 100% prior-ASCT rate (n = 662 excluding the brentuximab vedotin trial), the mOS was 28.1 months (95% CI 23.9–34.5), and the difference in mOS between brentuximab vedotin, chemotherapy, allo-SCT, and other therapies was 19.0 (95% CI 12.9–25.1; p < 0.0001), 9.4 (p > 0.05), and 6.8 months (95% CI 1.2–12.5; p = 0.0018), respectively. Conclusions: While some selection bias may occur when comparing trials with heterogeneous eligibility criteria, in the absence of randomized controlled trial data these results suggest brentuximab vedotin improves long-term survival and is associated with longer mOS in R/R HL post-ASCT compared with other therapies.